2017
DOI: 10.1177/2050312117709189
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medication adherence and the costs associated with a calendar blister pack intervention among hypertensive patients in Malaysia: A randomized controlled trial

Abstract: Objectives:To assess the efficacy and costs of a calendar blister packaging intervention used to improve medication adherence.Method:A parallel randomized controlled trial was conducted with 73 hypertensive patients (intervention group = 35, control group = 38) at Hospital Kulim, Malaysia, for 7 months.Results:The intervention group demonstrated a significant improvement in medication possession ratio (p < 0.05) and percentage of on-time refills (p < 0.01) compared to control group. In addition, there was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
5
1
3
Order By: Relevance
“…Therefore, we had a pool of patients with unpersonalized exposure toward learned skills, whereby merely reading and receiving information was insufficient to boost self-efficacy among stroke patients who were susceptible emotionally. In terms of blood-pressure control, our analysis contradicted recent studies that found poor medication-adherence rates negatively to affect blood-pressure control 36,5254. Discrepancies would have possibly occurred due to variance in study objectives, patient samples, and type of intervention.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, we had a pool of patients with unpersonalized exposure toward learned skills, whereby merely reading and receiving information was insufficient to boost self-efficacy among stroke patients who were susceptible emotionally. In terms of blood-pressure control, our analysis contradicted recent studies that found poor medication-adherence rates negatively to affect blood-pressure control 36,5254. Discrepancies would have possibly occurred due to variance in study objectives, patient samples, and type of intervention.…”
Section: Discussioncontrasting
confidence: 95%
“…It is also worth mentioning that studies on medication adherence in Malaysia were mainly conducted among the general adult population [53][54][55]. Our meta-analysis indicated that more than half of the elderly in Malaysia were not adherent to their medications.…”
Section: Discussionmentioning
confidence: 84%
“…Increased adherence has previously been demonstrated in trials of blister packaging programs for psychiatric medications and hypertensive medications. 11,12 A study investigating the use of blister packaging for multiple medications in elderly patients showed improvements in blood pressure and LDL measurements. 13 This broader application could subsequently lead to improved overall outcomes of our patient populations, particularly those at risk for more severe disease.…”
Section: Discussionmentioning
confidence: 99%